The hidden costs of virtual education: mental well-being in the digital age / Nor Syamaliah Ngah and Norazlin Abd Aziz - Ngah, Nor Syamaliah; Abd Aziz, Norazlin (Universiti Teknologi MARA, Negeri Sembilan, 2024)
The advent of online classes via social media profoundly affects the mental well-being of students, parents, and educators alike. This mode of instruction has the potential to exacerbate pre-existing mental health issues in individuals. Consider the plight of a child consigned to hours in front of a screen, devoid of the social interaction and recreational activities pivotal to their development. Concurrently, parents find themselves assuming the roles of educators, thereby intensifying their involvement in their children's scholastic endeavours. Furthermore, educators contend with heightened workloads and the imperative to deliver quality instruction absent conventional face-to-face interaction. The emergence of "Zoom fatigue," an idiomatic term coined amidst the COVID-19 era, underscores the toll exacted by prolonged online classes or video conferences. Though not clinically diagnosed, this phenomenon is palpable, particularly within the realm of virtual learning. The flood of information engendered by online classes, compounded by the strain of prolonged screen exposure, will cause mental exhaustion. Consequently, students grapple with heightened difficulty in assimilating new material, experiencing physical fatigue despite desk engagement. Such virtual learning fatigue constitutes a tangible substance for anxiety and stress, afflicting both students and educators alike.